Model of on-line control for the smart object by communication technologies; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Maksimova Yu. A. Yuliya Anatoljevna (2021, 2021)
Title screen